Aditivní výroba montážních a lisovacích přípravků technologií FDM - Gregora, Jan (Vysoké učení technické v Brně‎, Antonínská 548/1, 601 90 Brno, http://www.vutbr.cz/, 2023)
This bachelor thesis dealt with the design of fixtures for prototype assembly of thermoregulating modules. One of the aims of the thesis was to evaluate the suitability of using FDM printing for the production of prototype fixtures. FDM fixtures are intended to replace the metal fixtures used to date. The motivation for the use of additive manufacturing was to make production cheaper and faster within the prototype department of Schaeffler Production CZ, s.r.o. The effect of the surface loading on the 3D printed PETG material, which was chosen as the construction material within the scope of the work, was measured. The results of this measurement and the findings from the research part were used for FEA analysis and design of the product. The comparison of the cost-effectiveness and the speed of the prototype fixture production clearly shows that the use of additive technologies is better.
Keywords: assembly; fixture; přípravek; 3D printing; FDM; 3D tisk; montáž